Constructing a 3D-printable, bioceramic sheathed articular spacer assembly for infected hip arthroplasty. Issue 1 (March 2015) - Zhang, Yuan; Zhu, Jie; Wang, Zhibing; Zhou, Yue; Zhang, Xia
Graphical abstract: Highlights: The bone repair at the proximal defect is usually an ignored issue during hip arthroplasty revision. 3D printing technique holds great promise for fabricating enhanced synthetic bone graft substitutes. A 3D printable bioceramic spacer assembly may be a possible solution to the periprosthetic cases combined with critical bone defect. Abstract: Total hip arthroplasty (THA) has progressed to be one of the most cost-effective surgical procedures to relieve pain and restore function to the pathological hip. Official retrospective statistics revealed over 500, 000 cases of THA were performed per annum in the US alone, but failure cases brought about more than 40, 000 revision procedures among them. The revision surgery is usually hard to manipulate due to the formidable difficulty of repairing the critical bone defect. Plenty of attempts aiming at tackling this problem have been dedicated by both tissue engineering and clinical investigators. Despite of the initial success, it is still a great challenge to overcome atypical intertrochanteric and diaphyseal defects of proximal femur to reach a satisfied therapeutic outcome in terms of long-term survivorship of the prosthesis. Given the interdisciplinary integration of biomaterial fabrication, bone tissue engineering, rapid prototyping, and biomacromolecule/drug delivery, we propose a hypothesis to construct a biphasic articular spacer to reach the dual goal of infection control and bone regeneration in this study. To be specific, this complex is consisted by a geometry-specific calcium phosphate sheath, derived from computer aided design and low temperature 3D printing, and an axial bone cement pillar delivering antibiotics. Theoretically, this modularized spacer possesses the potency of enhanced osteogenesis, controlled release of specific drugs, and co-delivery of growth factors. If this strategy is validated, further effort can be made to strengthen the printability of calcium phosphate using the 3D printing technique, and to accelerate its translation from lab to clinics.